NAVIGATING THE IMPACTS OF CODE-SWITCHING IN ESP INSTRUCTION: INSIGHTS FROM LECTURERS AND STUDENTS - Setyowati, Yulis (University of Kuningan, 2023)
Numerous studies have been conducted to explore the phenomenon of code-switching. The results of this study carry significant implications for both lecturers and students, particularly in the context of ESP learning at the university level. This research aimed to delve into not only lecturers' perceptions but also students' attitudes and perceptions regarding the use of code-switching in EFL classrooms. Employing mixed methods design, specifically an explanatory sequential design, this study involved one lecturer and sixty students as participants. Data collection instruments included a questionnaire and semi-structured interviews. The findings revealed that the lecturers' code-switching is connected to the content being taught and the tasks being performed. They employ a system of secret codes as necessary. They employ code-switching to enhance communication and learning. Additionally, students had positive attitudes and perceptions toward the use of code-switching in ESP classrooms, as evidenced by the results of the students' questionnaire and semi-structured interviews. The majority of the pupils felt that their instructor's frequent use of code-switching benefited their education. They found that code-switching was crucial in the ESP classroom since it facilitated both teaching and learning. Moreover, it was acknowledged that code-switching can be used to improve their English skills. In addition, they reasoned that code-switching should be permitted in ESP classrooms so that lecturers can better assist their students and keep the lines of communication open between themselves and their pupils.